2015
DOI: 10.1007/s10815-015-0473-7
|View full text |Cite
|
Sign up to set email alerts
|

Policy of IVF centres towards oocytes affected by Smooth Endoplasmic Reticulum aggregates: a multicentre survey study

Abstract: Purpose The presence of Smooth Endoplasmic Reticulum aggregates (SERa) has been reported to be associated with adverse outcomes. An Alpha-ESHRE Consensus was published in 2011, strongly recommending to not inseminating affected oocytes. On the other hand, healthy babies have been born from oocytes presenting this dysmorphism. We surveyed several European IVF centres, to assess their attitudes concerning affected oocytes. Methods This survey is based on a computer format and includes questions regarding the fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
(39 reference statements)
0
11
0
1
Order By: Relevance
“…[5] Despite the recommendation, a multicentric survey published in 2015 to understand the change in policy of in vitro fertilization (IVF) units toward SERa+ oocytes found that just 14% of the surveyed centers discarded SERa+ oocytes and 43% of centers that did not discard oocytes followed up neonatal data. [6] Over 50% of centers either did not differentiate SERa+ oocytes or transferred SERa oocytes without neonatal follow-up. This study emphasized the fact that greater data monitoring and reporting of SERa+ oocyte outcomes was necessary to modify the current practice.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Despite the recommendation, a multicentric survey published in 2015 to understand the change in policy of in vitro fertilization (IVF) units toward SERa+ oocytes found that just 14% of the surveyed centers discarded SERa+ oocytes and 43% of centers that did not discard oocytes followed up neonatal data. [6] Over 50% of centers either did not differentiate SERa+ oocytes or transferred SERa oocytes without neonatal follow-up. This study emphasized the fact that greater data monitoring and reporting of SERa+ oocyte outcomes was necessary to modify the current practice.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, disturbances in morphology and function of these organelle associations may lead to a reduced oocyte competence for fertilization. In this regard, the presence of very large M-SER aggregates, sometimes related to gonadotropin hyperstimulation [21], has been generally associated with compromised embryo development and implantation [39,40], even though different opinions have been recently expressed [41][42][43]. On the contrary, underdeveloped M-SER aggregates have been found in a percentage of human mature oocytes subjected to vitrification [15] or to a slow freezing protocol based on the use of ethylene glycol as cryoprotectant agent [14], whereas other studies on slow-frozen oocytes treated with propanediol (PrOH) did not evidence qualitatively detectable ultrastructural alterations in M-SER aggregates [12,13,17].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this limited data, it has been recommended that oocytes with SERa should not be inseminated (Alpha Scientists in Reproductive Medicine and Eshre Special Interest Group of Embryology 2011) while laboratories have been urged to report SERa cases (Shaw-Jackson et al 2014) in order to more accurately assess the association of SERa with embryological and clinical outcomes. Nevertheless, a recently published multicenter survey showed that only few fertility centers respect these recommendations, with many practitioners transferring affected embryos without adequate data recording and follow-up, or simply not taking the presence of SERa into account at all (Van Beirs et al 2015). The aim of the present study was to report a case of complex chromosome rearrangement (CCR) with 2q31 deletion in a fetus originating from oocytes with SERa.…”
Section: Introductionmentioning
confidence: 98%